Green Supplier Evaluation and Selection in the Manufacturing Industry Using the Taguchi-VIKOR Methods - Adedeji, Wasiu Oyediran; Olowu, Joseph Kolawole; Adeniran, Mofoluwaso Kehinde; Oyelami, Seun; Adeboye, Busayo; Rajan, John; Jose, Swaminathan; Benrajesh, Pandiaraj; Oke, Sunday Ayoola (Universitas Atma Jaya Yogyakarta, 2025)
This paper proposes three methods for the joint optimization and selection of parameters in controlling the exhaust emission from logistics and packing industries, using the Taguchi-VIKOR, Taguchi-Pareto-VIKOR, and Taguchi-ABC-VIKOR methods. From the delta values of the Taguchi method, parameters F, E, A, B, C, and D were placed 1st, 2nd, 3rd, 4th, 5th, and 6th with delta values of 59.0066, 7.5263, 7.5261, 0.1150, 0.1113 and 0.1107, respectively. The delta ratio, delta variability, mean delta value and median delta value are 58.8959, 12.3993, and 3.8206, respectively. Furthermore, the optimal parametric setting is A1B1C1D1E1F1, which means 52 million dollars for revenue, 127 billion packing units, 0.77 optimal growth rate, 1.5 units of materials, 5581 kilotons of quantity consumed and 1 unit of carbon dioxide equivalent of packing materials. The methods are the cornerstone for evaluating the high-performing packing factor associated with greenhouse gas emissions and concurrently obtaining optimized values for packing enterprises to reduce emissions. Besides, and differently from earlier studies, methods such as Pareto, ABC, and VIKOR differentiate the alternative coupled Taguchi methods proposed in the literature. In addition, the following novel elements of the Taguchi method are introduced: Delta ratio, delta variability, mean delta value, delta/HOPV, delta/LOPV, and delta/AOPV. The results suggest that the developed methods adequately represent the optimized values and ranks obtained using the field data set from literature.